2020
DOI: 10.3390/pharmaceutics12080739
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Curcumin Enhanced by Microscale Discoidal Polymeric Particles in a Murine Asthma Model

Abstract: Curcumin is considered a potential anti-asthmatic agent owing to its anti-inflammatory properties. The objective of the present study was to prepare curcumin-containing poly(lactic-co-glycolic acid)-based microscale discoidal polymeric particles (Cur-PLGA-DPPs) and evaluate their anti-asthmatic properties using a murine asthma model. Cur-PLGA-DPPs were prepared using a top-down fabrication method. The prepared Cur-PLGA-DPPs had a mean particle size of 2.5 ± 0.4 μm and a zeta potential value of −34.6 ± 4.8 mV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…The group of Key has further explored the ability of DPNs to preferentially target the lungs following intravenous administration [98,99]. DPNs with a diameter of approximately 3 μm and a height of 1.5 μm were radiolabeled with 89 Zr and were administered intravenously to healthy Balb/c mice via tail-vein injection [98].…”
Section: Microparticles For Pulmonary Deliverymentioning
confidence: 99%
“…The group of Key has further explored the ability of DPNs to preferentially target the lungs following intravenous administration [98,99]. DPNs with a diameter of approximately 3 μm and a height of 1.5 μm were radiolabeled with 89 Zr and were administered intravenously to healthy Balb/c mice via tail-vein injection [98].…”
Section: Microparticles For Pulmonary Deliverymentioning
confidence: 99%
“…The expression of pro‐inflammatory parameters such as IL‐6, IL‐8, IL‐1β, and factor‐alpha (TNF‐α) in immortalized human airway basal cell line were improved by treatment with curcumin encapsulated in niosomes (Nio‐Curc) 55 . Administration of curcumin‐containing poly(lactic‐co‐glycolic acid) decreased epithelial hyperplasia and gablet cells in the airway of the murine asthma model 56 . Decreasing in Th2 and Th17 cells, serum levels of IL‐4 and IL‐13, as well as increasing in the mRNA expression level of M1 macrophage‐related inflammatory factors including IL‐6, iNOS, and IL‐1β were indicated by treatment with curcumin (200 mg/kg) in asthmatic mice 57 .…”
Section: Resultsmentioning
confidence: 99%
“…The results of the ANOVA test (Table 4) showed that the P-value was lower than 0.05 for all responses and P for the lack of fit was greater than 0.05 for all responses, confirming that the proposed model is adequate, reliable, and has a good predictive power. (1) Regression coefficient; (2) predictive power of the model; (3) degrees of freedom; (4) sum of squares; (5) mean of square (variance); (6) Fisher's ratio; (7) probability; (8) particle size (µm); (9) particle size distribution (%); (10) drug loading (%); (11) entrapment efficiency (%); (12) yield (%); (13)(14)(15)(16)(17) percentage of curcumin released after 2 h, 4 h, 6 h, 12 h, and 24 h (%).…”
Section: Summary Of Fitmentioning
confidence: 99%
“…CQA (1) Predicted (1) Critical quality attribute; (2) particle size (%); (3) particle size distribution (%); (4) drug loading (%); (5) entrapment efficiency (%); (6)(7)(8)(9) percentage of curcumin released after 2 h, 4 h, 6 h, and 12 h (%).…”
Section: Establishment Of the Design Space And Validation Of The Modelmentioning
confidence: 99%
See 1 more Smart Citation